EVALUASI PENGELOLAAN KEUANGAN DESA DI DESA PA'KEBUAN BERDASARKAN PERMENDAGRI NO. 20 TAHUN 2018 - Agus Riyanto; Elyana Elyana; Hendrikus Gantur (Economic Faculty, University of Widya Gama Mahakam Samarinda, 2023)
This type of research is qualitative research, where the focus of the research is participatory and transparency in village financial management in Pa'Kebuan Village, where the informants in this study are the village head, BPD members, village apparatus and hamlet heads. The results of this study refer to the Village Financial Management System Analysis in Pa'Kebuan Village, Krayan Timur District, Nunukan Regency, North Kalimantan Province using a participatory and transparent approach. The management of the village fund budget in Pa'Kebuan Village has very high community participation. The community's involvement in the planning varied widely, some actually discussed development, some came because they wanted to take part in development activities, and some other people came just to enliven it. However, as a whole the Pa'Kebuan Village government has attempted to initiate meetings with the community in village fund management planning activities. planning for village financial management, the village government is very transparent in explaining the amount of the budget managed by the village government so that planning involves elementsthe village government, BPD and the community are able to synchronize with development needs and empowerment with the amount of the budget managed by Pa'Kebuan Village.